Diachronic Analysis of some Urban Spaces in Valencia by Means of Rephotography (diségno, 2019)
The main objective of this research work is the application and study of a photographic technique called rephotography, which consists of taking a photograph from the same viewpoint as another picture that was taken in the past. This technique allows analyzing the evolution of the photographed scene over the time. To this end, a compilation of ancient photographs of different urban scenarios of the city of Valencia has been carried out. These photographs have been studied by means of a thorough graphic analysis, carried out by applying the laws of perspective, in order to accurately restitute the point of view of each picture. This process allows the accurate matching of the composition of current re-photographs to the older ones. After that, a comparative study between present and historical photographs was carried out in order to analyze the changes that these different urban scenarios have suffered throughout history. The graphic results of this research are intended to awaken the interest of the viewer, who can easily understand this evolution. This study also helps to recover the historical memory of places that have already disappeared or have undergone a profound transformation.
Keywords: Rephotography; perspective; photographic restitution; diachronic analysis